A Morphometric Analysis Of Genus Tylonycteris (Bamboo Bat) In Selected Localities In Malaysia - Fatin Nadzirah, Roomdzi (Universiti Malaysia Sarawak (UNIMAS), 2014)
The morphological study was performed on 42 individuals of bamboo bat (Genus Tylonycteris). This study was carried out to determine any morphological variation within species of different localities and to identify the characters that are useful for species identification of species in this genus. Sixteen external characters and 17 craniodentals characters were measured and subjected to morphological analysis. Discriminant function analysis (DFA) was done for separated external and craniodental characters. The FA was suggested as the best external predictors for T. pachypus while for T. robustula external predictors, the highest character loadings for function I was D3P IL and for function 2 was D5MCL. ZW was suggested as the best internal predictors for T. pachypus while for T. robustula, the highest character loadings for function I was lOW and ZW for function 2. The clustering analysis has been done using Paleontological Statistic (PAST) version 3.0. The findings show that there is a morphological variation within the study species.